2022
DOI: 10.3934/neuroscience.2022008
|View full text |Cite
|
Sign up to set email alerts
|

The <i>RET</i> gene encodes RET protein, which triggers intracellular signaling pathways for enteric neurogenesis, and <i>RET</i> mutation results in Hirschsprung's disease

Abstract: <abstract> <p>Enteric neurons and ganglia are derived from vagal and sacral neural crest cells, which undergo migration from the neural tube to the gut wall. In the gut wall, they first undergo rostrocaudal migration followed by migration from the superficial to deep layers. After migration, they proliferate and differentiate into the enteric plexus. Expression of the Rearranged During Transfection (<italic>RET</italic>) gene and its protein RET plays a crucial role in the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 124 publications
0
4
0
Order By: Relevance
“…RET protein has three different subtypes, named RET51, RET43, and RET9. Moreover, Bhattarai et al ( 37 ) showed that interactions between RET protein and its ligands can control the survival, migration, proliferation, differentiation, and maturation of vagal and sacral neural crest cells. Nagy et al ( 38 ) demonstrated that excessive stimulation of RET al.…”
Section: Discussionmentioning
confidence: 99%
“…RET protein has three different subtypes, named RET51, RET43, and RET9. Moreover, Bhattarai et al ( 37 ) showed that interactions between RET protein and its ligands can control the survival, migration, proliferation, differentiation, and maturation of vagal and sacral neural crest cells. Nagy et al ( 38 ) demonstrated that excessive stimulation of RET al.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, RET rearrangements are described in papillary thyroid carcinoma, non-small cell lung carcinoma, and other sporadic types of cancers. Gain of function aberrations are present mostly in oncogenic diseases, but RET may also be inactivated, causing Hirschsprung’s disease, congenital kidney or urinary tract anomalies, or innate central hypoventilation syndrome [ 13 , 14 ].…”
Section: Ret Protein and Activitymentioning
confidence: 99%
“…These are most commonly described in Hirschsprung’s disease (HSCR), a congenital malformation with the presence of aganglionosis of the gastrointestinal tract. RET mutations occur in approximately 50% of familial and 10–20% of sporadic cases of HSCR [ 14 , 49 , 50 , 51 ]. There are different mechanisms of RET impairment and consequently loss of its function, mainly depending on the localization of mutation.…”
Section: Mutationsmentioning
confidence: 99%
“…It’s inherited in an autosomal dominant manner and features medullary thyroid carcinoma, hyperparathyroidism, and pheochromocytoma [ 4 , 5 ]. The condition arises from a RET (rearranged during transfection variant) [ 6 ] gene variant on chromosome 10q11.2, which often results in medullary thyroid carcinoma, typically diagnosed before 35 years [ 7 – 9 ]. Pheochromocytoma, another manifestation of MEN2A, affects fewer than half of patients, yet bilateral pheochromocytoma in MEN2A is not uncommon, occurring in 50–80% of cases [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%